Interactions of hydroxyapatite with proteins and its toxicological effect to zebrafish embryos development. - Zhen Xu (Public Library of Science (PLoS), 2012)
The increased application of nanomaterials has raised the level of public concern regarding possible toxicities caused by exposure to nanostructures. The interactions of nanosized hydroxyapatite (HA) with cytochrome c and hemoglobin were investigated by zeta-potential, UV-vis, fluorescence and circular dichroism. The experimental results indicated that the interactions were formed via charge attraction and hydrogen bond and obeyed Langmuir adsorption isotherm. The two functional proteins bridged between HA particles to aggregate into the coralloid form, where change of the secondary structure of proteins occurred. From effects of nanosized HA, SiO(2) and TiO(2) particles on the zebrafish embryos development, they were adsorbed on the membrane surface confirmed by the electronic scanning microscopy. Nano-HA aggregated into the biggest particles around the membrane protein and then caused a little toxicity to development of zebrafish embryos. The SiO(2) particles were distributed throughout the outer surface and caused jam of membrane passage, delay of the hatching time and axial malformation. Maybe owing to the oxygen free radical activity, TiO(2) caused some serious deformity characters in the cardiovascular system.